PENGARUH DOSIS PEMUPUKAN TERHADAP HASIL TIGA KULTIVAR CABAI MERAH THE EFFECT OF FERTILIZATION DOSAGES ON YIELD OF THREE CULTIVARS OF SWEET PEPPER - , Murwito; , Sakhidin; Hidayat, Ponendi (Pembangunan Pedesaan, 2010)
Stabilizing the production of sweet pepper is importance to eliminate the fluctuation of supply and price in the market. One of these efforts is cultivation by using good cultivars and optimum fertilization. There were two treatments, namely cultivars (Hot Beauty, TM 888, and TM 999) and fertilization (600 kg/ha NPK +150 kg/ha ZA, 900 kg/ha NPK+225 kg/ha ZA, 1200 kg/ha NPK+300 kg/ha ZA, and 1500 kg/ha NPK+375 kg/ha ZA). This research used Randomized Completely Block Design by 3 replications. Result of the research showed that Hot Beauty, TM 999, and TM 888 cultivars varied in plant height, number of fruit/plant, fruit length, fruit diameter, fresh weight fruit/plant, and fresh weight fruit/plot, but generally Hot Beauty gave the highest yield. The increasing dosage of NPK and ZA would increase fruit length and diameter. Interaction between cultivar and fertilization did not affect significantly on all observed variables.